Exploring sleep heart rate variability: linear, nonlinear, and circadian rhythm perspectives - Hasegawa, Mizuki; Sasaki, Mayuko; Umemoto, Yui; Hayashi, Rio; Hatanaka, Akari; Hosoki, Marino; Farag, Ahmed; Matsuura, Katsuhiro; Yoshida, Tomohiko; Shimada, Kazumi; Hamabe, Lina; Takahashi, Ken; et al. (Frontiers in Veterinary Science, 2024)
Background: Heart rate variability (HRV) is believed to possess the potential for disease detection. However, early identification of heart disease remains challenging, as HRV analysis in dogs primarily reflects the advanced stages of the disease. Hypothesis/Objectives: The aim of this study is to compare 24-hour HRV with sleep HRV to assess the potential utility of sleep HRV analysis. Animals: Thirty healthy dogs with no echocardiographic abnormalities were included in the study, comprising 23 females and 7 males ranging in age from 2 months to 8 years (mean [standard deviation], 1.4 [1.6]). Methods: This study employed a cross-sectional study. 24-hour HRV and sleep HRV were measured from 48-hour Holter recordings. Both linear analysis, a traditional method of heart rate variability analysis, and nonlinear analysis, a novel approach, were conducted. Additionally, circadian rhythm parameters were assessed. Results: In frequency analysis of linear analysis, the parasympathetic index nHF was significantly higher during sleep compared to the mean 24-hour period (mean sleep HRV [standard deviation] vs. mean 24 hours [standard deviation], 95% confidence interval, P value, r-family: 0.24 [0.057] vs. 0.23 [0.045], 0.006-0.031, P = 0.005, r = 0.49). Regarding time domain analysis, the parasympathetic indices SDNN and RMSSD were also significantly higher during sleep (SDNN: 179.7 [66.9] vs. 156.6 [53.2], 14.5-31.7, P < .001, r = 0.71 RMSSD: 187.0 [74.0] vs. 165.4 [62.2], 13.2-30.0, P < .001, r = 0.70). In a geometric method of nonlinear analysis, the parasympathetic indices SD1 and SD2 showed significantly higher values during sleep (SD1: 132.4 [52.4] vs. 117.1 [44.0], 9.3-21.1, P < .001, r = 0.70 SD2: 215.0 [80.5] vs. 185.9 [62.0], 17.6-40.6, P < .001, r = 0.69). Furthermore, the circadian rhythm items of the parasympathetic indices SDNN, RMSSD, SD1, and SD2 exhibited positive peaks during sleep. Conclusions: The findings suggest that focusing on HRV during sleep can provide a more accurate representation of parasympathetic activity, as it captures the peak circadian rhythm items.